CD1c(+) blood dendritic cells have Langerhans cell potential - Milne, Paul (Blood, 2015)
Langerhans cells (LCs) are self-renewing in the steady state but repopulated by myeloid precursors after injury. Human monocytes give rise to langerin-positive cells in vitro, suggesting a potential precursor role. However, differentiation experiments with human lineage-negative cells and CD34(+) progenitors suggest that there is an alternative monocyte-independent pathway of LC differentiation. Recent data in mice also show long-term repopulation of the LC compartment with alternative myeloid precursors. Here we show that, although monocytes are able to express langerin, when cultured with soluble ligands granulocyte macrophage colony-stimulating factor (GM-CSF), transforming growth factor β (TGFβ), and bone morphogenetic protein 7 (BMP7), CD1c(+) dendritic cells (DCs) become much more LC-like with high langerin, Birbeck granules, EpCAM, and E-cadherin expression under the same conditions. These data highlight a new potential precursor function of CD1c(+) DCs and demonstrate an alternative pathway of LC differentiation that may have relevance in vivo.